Use of Social Science Materials in Teaching Within the Standard Generalist Law Curriculum: A Criterion for Their Refined Integration - Leigh Hunt Greenhaw (Washington University Law Quarterly, 1981)
The thesis of this Article is that the primary and unique task of legal education is furthering insight into the distinct pattern of relationship among theory, norms, and empirical fact.
Keywords: Case teaching method; Law schools; Legal education; Social sciences; United States